HUMAN CAPITAL CONVERGENCE IN PUNJAB - Fatima, Nusrat (Journal of Peace, Development and Communication, 2022)
Ever since the convergence hypothesis has emerged, debate on convergence has remained great concern for economists. The literature comes up with mixed evidence on convergence between economies, regions or group of economies. The main purpose of undertaking this research is to examine the convergence among human capital indicators between the districts of Punjab during 2003 to 2019. The study also finds the rate of convergence in order to know the average speed with which the human capital is merging/converging in Punjab. This study utilized data from two government surveys, MICS (Multiple indicator cluster survey) and PSLM (Pakistan social and living measurement survey). Following endogenous growth models simple OLS regressions and some other measurements like Mean, SD and CV have also been used. Results of this study witnessed the evidence of convergence in human capital indicators and hence economic growth among the districts of Punjab. As education and health are fundamental ingredients of human capital so, there is need of efficient Government policies and their proper implementation.